Possible Association of the GSK3β Gene with the Anxiety Symptoms of Major Depressive Disorder and P300 Waveform - Liu, Sha (Mary Ann Liebert, Inc., 2012)
Glycogen synthase kinase-3β (GSK3β) may play an important role in the brain of patients with major depressive disorder (MDD); therefore, we investigated whether the GSK3β gene is involved in the etiology of MDD and whether it affects MDD endophenotypes. Three single-nucleotide polymorphisms (SNPs) (rs6438552, rs7633279, and rs334558) were genotyped in 559 MDD patients and 486 healthy controls. To explore quantitative traits of MDD, we analyzed the association of these SNPs with the factor scores of the 17-item Hamilton Depression Rating Scale (HAMD-17) and the Hamilton Anxiety Rating Scale (HAMA). We also determined the effects of these SNPs on the measurement of the P300 wave. Although no significant association between GSK3β SNPs and MDD was found, some genotypes and haplotypes were associated with anxiety symptoms in MDD. The three SNPs were associated with the HAMA total score and with the HAMD anxiety and somatization factor score (p<0.05). Three-locus haplotype analysis showed the C-T-G carriers to have a strong association with the HAMA total score (p=0.032). Moreover, the P300 latency and amplitude were also associated with GSK3β genotypes. The individuals with the T allele genotype, both in rs6438552 and rs7633279, have a longer P300 latency than those carrying the C/C (p=0.04) and A/A genotype (p=0.013). The individuals with the G/G genotype in rs334558 have a lower amplitude than those carrying the A allele genotype (p=0.007). Our findings show, for the first time, that GSK3β polymorphisms may play an important role in MDD endophenotypes, especially in anxiety symptoms.